Выбор структурных акцентов активизации развития промышленности Украины - Якубовский, Н.Н.; Солдак, М.А. (Економіка промисловості, 2017)
Статья посвящена проблемам поиска отраслевого вектора структурной политики промышленности Украины. На основе предложенных критериев дана оценка каждому виду промышленной деятельности. Осуществлена рейтинговая оценка приоритетности отраслей промышленности для предоставления государственной поддержки. Статтю присвячено проблемам пошуку галузевого вектора структурної політики промисловості України. На основі запропонованих критеріїв надано оцінку кожному виду промислової діяльності. Здійснено рейтингову оцінку пріоритетності галузей промисловості для надання державної підтримки. The search for the sectoral vector of structural policies is still urgent for Ukrainian industry. Each of the sectors bears the relevant economic and social burden and therefore has a reason to claim the state support. To some extent such support exists. However, it is provided not according to the strategy of socio-economic development of the country, which would give it the economic and legal framework, but by lobbying the private interests of certain business groups. Further conservation of this trend can only deepen the conflict of interests of the society and business, and as a result slow the process of modernization and revitalization of the industry.State policy strategy on supporting certain sectors and industries should be open and scientifically grounded. The support should be based on the sectors able to provide further structural transformation of the industrial complex, in particular improving the technological level, overcoming the raw material orientation, and deepening technological processing with an increase in value added. Therefore, the purpose of the article is to develop new approaches to the identification of priority industrial activities, the results of which will help to manage the process of changes in the structure of production directed to the creation of a modern industrial complex able to raise the country’s competitiveness and provide the achievement of sustainable economic growth. To choose these sectors, the following criteria are offered: effi-ciency, i.e., a share of GDP that the industrial sector generates per hryvnia; manufacturing activity, namely, how rapidly the industry develops due to competitive conditions and the demand for its products; market position, in particular export orientation and import dependence of the industry in providing domestic market requirements; innovativeness, i.e., how the development of the activity will contribute to the modernization of the domestic industry in accordance with global trends.The methodology of the integral measurement of priority activities is based on the scoring for each of the criteria adopted and their total value. The rating estimation of the priority of certain industrial activities for providing the state support is the result of the study. The proposed approach to the definition of priority will allow managing the process of structural changes and assessing the potential effect of the industrial policy on improving the industrial structure.